Processes that influence the experiences of children living with mothers that have HIV: two case studies - Castelletto, Simona (Rhodes University, Faculty of Humanities, Department of Psychology, 2004)
Maternal HIV-infection is considered to be a threat to the psychosocial development of AIDS-affected children. In South Africa, AIDS-affected children may be particularly vulnerable due to the unprecedented effects of the HIV/AIDS epidemic on the breakdown of family and community resources in already disadvantaged communities. The aim of this study was to explore the contextualised experiences of two children living with mothers who have HIV by conducting two case studies. Mother-child dyads were recruited from local HIV/AIDS centres and informed consent was obtained. The mothers were in the minor symptomatic phase of HIV-infection and the children were uninfected and aged between 10 and 12 years. Through semi-structured interviewing, the mothers provided background and contextual information about the children. Play techniques were used in the child interviews to encourage the introduction and exploration of issues salient to the children. Play facilitated engagement around sensitive and potentially anxiety-provoking material. A key issue for the children was their concerns about the anticipated deaths of their mothers. The children held misconceptions about the transmission of HIV/ AIDS. They feared HIV/AIDS and expected that others would have negative perceptions of them. Family processes such as secrecy and avoidance around HIV/AIDS-related issues were understood to perpetuate the children's fears and false beliefs in a broader community context that stigmatised HIV/AIDS. It was argued that the mothers' shame over HIV-infection and their need to protect their relationship with their children compromised their ability to communicate openly with their children and to offer them meaningful emotional support. Limited parental involvement was identified as the key contextual process that engendered vulnerability in the children, as they were isolated within and beyond the family. Recommendations to address the processes that engendered vulnerability in the children are discussed.
Keywords: AIDS (Disease) in women; AIDS (Disease) -- Social aspects -- South Africa; HIV infections -- Social aspects -- South Africa; Mothers and daughters -- Social aspects; Mothers and sons -- Social aspects; AIDS (Disease) in children -- Social aspects -- South Africa